2002
DOI: 10.1007/s10123-002-0067-y
|View full text |Cite
|
Sign up to set email alerts
|

Survival of several Rhizobium/Bradyrhizobium strains on different inoculant formulations and inoculated seeds

Abstract: The effect of a variety factors on the survival of several rhizobia strains on inoculants and inoculated seeds has been evaluated. Since the rhizobia strains showed different cell-density-evolution patterns on peat-based inoculants and on inoculated seeds, several inoculant formulations with highly effective Rhizobium/Bradyrhizobium strains (for Lupinus, Hedysarum, Phaseolus and Glycine max.) were monitored under the following storage conditions: (a) the inoculants were kept refrigerated (at 4 degrees C), or (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
8

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 16 publications
1
20
0
8
Order By: Relevance
“…Antoun et al (1998) reported that non-leguminous plants react to the presence of bradyrhizobia and rhizobia on their rhizospheres; however, the growth-promoting effect depended on the bacterial strains isolated and their endogenous PGP abilities (Galleguillos et al 2000;Vessey 2003). In our study, the environment proved to be a very important component for plant growth promotion using rhizobia inoculation because several rhizobia isolates promoted the plant growth in sterile conditions, but they were unable to reproduce the same effect in non sterile, rich nutrient conditions (Table 6; Temprano et al 2002;Bennett et al 2003). This observation can be attributed to bacterial persistence and competition in the soil and to the amount of nutrients present in very rich soil conditions (Hagen et al 1997;Krasova-Wade et al 2006;Al-Khaliel 2010;Costa et al 2013).…”
Section: Discussionmentioning
confidence: 80%
“…Antoun et al (1998) reported that non-leguminous plants react to the presence of bradyrhizobia and rhizobia on their rhizospheres; however, the growth-promoting effect depended on the bacterial strains isolated and their endogenous PGP abilities (Galleguillos et al 2000;Vessey 2003). In our study, the environment proved to be a very important component for plant growth promotion using rhizobia inoculation because several rhizobia isolates promoted the plant growth in sterile conditions, but they were unable to reproduce the same effect in non sterile, rich nutrient conditions (Table 6; Temprano et al 2002;Bennett et al 2003). This observation can be attributed to bacterial persistence and competition in the soil and to the amount of nutrients present in very rich soil conditions (Hagen et al 1997;Krasova-Wade et al 2006;Al-Khaliel 2010;Costa et al 2013).…”
Section: Discussionmentioning
confidence: 80%
“…The procedure is laborious because of large volume; there is high energy cost; it is time consuming, and most importantly, some organic materials change their chemical properties and may produce toxic substance to some bacteria during autoclaving. Still, autoclaving is favorable for several rhizobia strains that survive in sterile peat inoculant far better than under non-sterile conditions (Temprano et al 2002).…”
Section: Sterilizationmentioning
confidence: 99%
“…Biopolímeros (polivinil álcool -PVA, polivinil pirrolidona -PVP, polietileno glicol -PEG, bem como o alginato, a goma xantana e o amido); são adicionados para neutralizar compostos tóxicos, como os compostos fenólicos liberados na rizosfera (TITTABUTR et al, 2007). Também possuem uma boa ligação com a água e atuam como agente hidratante; além de melhorar a adesão das células microbianas à semente (TEMPRANO et al, 2002). 3.…”
Section: Inoculantes Agrícolas Para Plantas Não Leguminosas: Biofertiunclassified